Screening for in Vitro Biofilm Formation Ability of Locally Isolated Uropathogenic Escherichia coli (UPEC) - A. Ebraheem, Abdalla; A. Alwendawi, Shadan (Iraqi Journal of Science, 2023)
Seventy-six urine specimens were collected from of patients suffering from recurrenturinary tract infections (UTIs). Specimens were bacteriologically analyzed, fifty(65.8%) of isolated bacterial strains were belonged to E.coli. 100% of isolateduropathogenic E.coli (UPEC)strains displayed a biofilm positive phenotype underoptimized condition using microtiter plate assay. 21 of E.coli strains classified as highlypositive biofilm producers (42%), and 29 (58%) as weakly positive biofilm producers.